Laboratory handling of epididymal and testicular spermatozoa: What can be done to improve sperm injections outcome - Sandro C Esteves; Alex C Varghese (Wolters Kluwer Medknow Publications, 2012)
Spermatozoa from azoospermic males can be retrieved from either the epididymis or the testis, depending on the type of azoospermia, using different surgical methods such as percutaneous epididymal sperm aspiration (PESA), testicular sperm aspiration (TESA), testicular sperm extraction (TESE), and microsurgical testicular sperm extraction (micro- TESE). After collecting the epididymal fluid or testicular tissue, laboratory techniques are used to remove contaminants, cellular debris, noxious microorganisms, and red blood cells. Processed spermatozoa may be used for intracytoplasmic sperm injection or eventually be cryopreserved. However, spermatozoa collected from either the epididymis or the testis are often compromised and more fragile than ejaculated ones. Therefore, sperm processing techniques should be used with great caution to avoid jeopardizing the sperm fertilizing potential in treatment cycles. In this review, we describe the current methods for processing surgically-retrieved specimens, either fresh or frozen- thawed, and provide the tips and pitfalls for facilitating the handling of such specimens. In addition, we present the available laboratory tools to aid in the identification of viable immotile spermatozoa to be used in conjunction with assisted reproductive techniques. Review of the literature was carried out using PubMed and Science Direct search engines.